2016
DOI: 10.1158/0008-5472.can-15-2340
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A1 and P450 Aromatase Promote Metastatic Homing and Growth of Stem-like Prostate Cancer Cells in the Bone Marrow

Abstract: Bone metastasis is a leading cause of morbidity and mortality in prostate cancer. While cancer stem-like cells have been implicated as a cell of origin for prostate cancer metastasis, the pathways that enable metastatic development at distal sites remain largely unknown. In this study, we illuminate pathways relevant to bone metastasis in this disease. We observed that cyclin A1 (CCNA1) protein expression was relatively higher in prostate cancer metastatic lesions in lymph node, lung, and bone/bone marrow. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…Therefore, to delineate the role of MTA1 in bone metastasis, we utilized the experimental bone metastasis model with injections of cells into the left cardiac ventricle of athymic mice (Chong Seow Khoon, 2015; Holzapfel et al ., 2014; Miftakhova et al ., 2016; Rosol et al ., 2004). Metastases were monitored by weekly bioluminescence imaging until day 34, when mice were sacrificed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to delineate the role of MTA1 in bone metastasis, we utilized the experimental bone metastasis model with injections of cells into the left cardiac ventricle of athymic mice (Chong Seow Khoon, 2015; Holzapfel et al ., 2014; Miftakhova et al ., 2016; Rosol et al ., 2004). Metastases were monitored by weekly bioluminescence imaging until day 34, when mice were sacrificed.…”
Section: Resultsmentioning
confidence: 99%
“…Metastatic growth was found in the lymph node, lung, and liver in subcutaneous and orthotropic xenograft mouse models after the induction of CCNA1 over-expression in PC3 cells. Regina reported that CCNA1 interacts with Erαto promote breast cancer progression in xenograft mouse models [22]. SDS stimulation for 1.5 h caused a high level of CCNA1 expression, which is closely related with the development of cancers.…”
Section: Discussionmentioning
confidence: 97%
“…E 2 acts on local stromal and epithelial cells and there is paracrine regulation of its production, but this is lost in PCa. Increased aromatase expression in metastatic PCa lesions has been demonstrated (Miftakhova et al 2016). Estrogens along with other non-androgen ligands may be able to activate mutated ARs as one mechanism of 24:8 castrate resistance (Leach et al 2016).…”
Section: Effects Of Estradiol On Prostate Cancermentioning
confidence: 99%